Biomimetic Catalytic Oxidation of Hantsch 1,4-Dihydropyridines Using [Bis-(salicylaldehye)-4-methyl-1,2-phenylenediimine]- Mn(III) Chloride/Sodium Periodate Under Mild Conditions - MONTAZEROZOHORI, M.; NASR-ESFAHANI, M.; JOOHARI, S.; HAGHIGHAT, NASRIN (Asian Journal of Chemistry, 2010)
[Bis(salicylaldehye)-4-methyl-1,2-phenylenediimine]Mn(III) chloride [Mn(III)-BSMP] as biomimetic catalyst was synthesized and identified by spectral and analytical data. A variety of Hantzsch 1,4-dihyropyridines were subjected by a catalytic amount of this catalyst in the presence of sodium periodate as convenient and mild oxidant to afford the related pyridine derivatives in good to high yields at room temperature. The effects of some operational parameters such as amount of catalyst, the type of oxidant, necessity of axial ligand and solvent effect were investigated.